Validation of the recovery experience questionnaire in Malaysian context - Muhamad Nasharudin, Nurfazreen Aina (Human Resource Management Academic Research Society, 2023)
Recovery is an essential process to eliminate stress due to work demands. However, a valid and reliable instrument to examine different dimensions of recovery experience among Malaysian workers is currently unavailable. Thus, the purpose of the present study is to examine the psychometric properties of an existing and well-validated survey instrument on recovery in the work setting that was adapted for employees in Malaysia. The Recovery Experience Questionnaire (REQ) was empirically tested among 353 Malaysian employees. Confirmatory factor analysis (CFA) and measurement invariance were used for analysis. Results showed the four-factor structure of the instrument, consisting of psychological detachment, relaxation, control, and mastery, was supported. Internal consistencies of all subscales were satisfactory, and the instrument was invariant across gender, age, type of occupation, and over time. The present study provides initial evidence that the REQ is a valid and reliable instrument to simultaneously measure psychological detachment, relaxation, control, and mastery among workers in Malaysia.